DIAGNOSTIC VALUE OF CFT/LCFT FOR CATTLE MORAXELLOSIS - N. P. Ivanov,; R. S. Sattarova,; F. A. Bakiyeva,; K. M. Shynybaev,; B. Zh. Issakulova, (Scientific Journal of Pedagogy and Economics, 2019)
In our country, moraxellosis has not previously been registered and immunological tests have not been tested (RSK and RDSK). Timely diagnosis of morax is a major component of antiepizootic measures. Currently, the diagnosis of moraxcellosis is based on the epidemiological data and the clinical picture. Early signs of the disease can only be detected by immunological tests. In this regard, we have tested the serological reactions, in particular the CFT and LCFT and given a comparative diagnostic value.